2017
DOI: 10.1515/opis-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Students’ Privacy Paradox and Privacy Protection Behavior

Abstract: Abstract:In this exploratory study, we investigate the factors affecting two opposite types of online privacy behavior: 1) online privacy paradox, i.e. a mismatch between users' online privacy attitudes and their online privacy behavior; and 2) online privacy protection. To assess these two types of behavior, we devised a new direct scale comprising 25 items explicitly highlighting benefits and risks of the examined behavior. Various factors related to online privacy and anonymity were considered in light of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 65 publications
3
9
0
1
Order By: Relevance
“…These results seem to be in accordance with some of the above studies (Akhter, 2014;Awad & Krishnan, 2006;Castañeda & Montoro, 2007;Heirman et al, 2013;Hoffman et al, 1999;J. K. Lee & Letho, 2010;Phelps et al, 2001;Phelps et al, 2000;Potoglou et al, 2015;Taylor et al, 2009;Weinberger et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results seem to be in accordance with some of the above studies (Akhter, 2014;Awad & Krishnan, 2006;Castañeda & Montoro, 2007;Heirman et al, 2013;Hoffman et al, 1999;J. K. Lee & Letho, 2010;Phelps et al, 2001;Phelps et al, 2000;Potoglou et al, 2015;Taylor et al, 2009;Weinberger et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The personalization-privacy tradeoff was also examined in a wider perspective by studies which investigated the discrepancy between users' online privacy attitudes and their actual behavior reflected the opposite -the "privacy paradox" (Barnes, 2006;Norberg et al, 2007). These studies (e.g., Acquisti & Gross, 2006;Debatin et al, 2009;Dienlin & Trepte, 2015;Gross & Acquisti, 2005;Taddicken, 2014;Tufekci, 2008;Weinberger et al, 2017) explored the dichotomy between privacy concerns and self-disclosure. This dichotomy was most apparent in the setting of social networks.…”
Section: The Privacy Paradox and Th E Factors Th At Affect Self-disclmentioning
confidence: 99%
“…The responses were coded on a 1-5 Likert scale and then were averaged for each indicator separately. The questions were based on previous research conducted on user privacy concerns (Weinberger et al, 2017) and information security surveys (e.g. Aydin and Chouseinoglou, 2013;Talib et al, 2010).…”
Section: Research Variables and Validation Methodsmentioning
confidence: 99%
“…Privacy has always been a major concern associated with the commercial information technology and particularly with regard to the issue of personalization (Sutanto et al, 2013) -"the ability to provide content and services that are tailored to individuals based on knowledge about their preferences and behaviors" (Adomavicius and Tuzhilin, 2005). The trade-off between online privacy and self-disclosure was investigated in past studies (Taddicken, 2014;Weinberger et al, 2017;Weinberger and Bouhnik, 2018). Some of which focused specifically on the trade-off between online personalization and online privacy protection (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords music streaming applications, personal information management, privacy, personalization was investigated in past studies (Fogel & Nehmad, 2009;Hoy & Milne, 2010;Milne, Rohm, & Bahl, 2004;Paine, Reips, Steiger, Joinson, & Buchanan, 2007;Taddicken, 2014;Weinberger & Bohnik, 2018;Weinberger, Bouhnik, & Zhitomirsky-Geffet, 2017;Wills & Zeljkovic, 2011), some of which focused specifically on the tradeoff between online personalization and online privacy protection (e.g., Weinberger & Bouhnik, 2018). Many of the studies showed that users are concerned with their online privacy and wish to protect it (e.g., Paine et al, 2007;Wills & Zeljkovic, 2010).…”
Section: Introductionmentioning
confidence: 99%